"You won't find me living in a cocoon - that's why I decided to set up shop in Sydney" [John Howard on the steps of Kirribilli House] - Pryor, Geoff, 1944- (1996)
Rejecting the 'isolation' of Canberra, newly installed Prime Minister John Howard chooses instead to forsake the Lodge in Canberra for the sensational harbour views of Kiribilli House in Sydney. What a sacrifice!--Information provided by Geoff Pryor.
Title devised by cataloguer.
Published in the Canberra Times on 28 August 1996.
Part of the Pryor collection of cartoons and drawings.
Also available online
Keywords: Howard, John, -- 1939- -- Caricatures and cartoons; Kirribilli House (Kirribilli, N.S.W.) -- Caricatures and cartoons